A Trauma Analysis of Juliet Sykes’s Character in “Before I Fall” (A Novel Written by Lauren Oliver) - Salshabila Sawitri A. Paputungan; Novi Rusnarty Usu; Farid Muhamad (Transbahasa, 2025)
This research explores the psychological trauma experienced by Juliet Sykes, a secondary character in Before I Fall (2010) by Lauren Oliver, through the lens of Sheila Cavanagh’s cultural-psychoanalytic trauma theory. The study analyzes dialogues and narrative descriptions that reveal signs of trauma to understand how Juliet’s suffering is represented in the novel. The results show that Juliet endures both Type II and complex trauma, stemming from continuous bullying, humiliation, and long-term social rejection. Her psychological responses manifest as feelings of powerlessness, recurring memories of distressing experiences, unstable emotions, challenges in constructing a coherent sense of self, and tendencies toward isolation. Moreover, the narrative portrays Juliet’s trauma as not only a mental or emotional disruption but also as an embodied and socially conditioned experience. This interpretation supports Cavanagh’s assertion that trauma is relational and performed within cultural and interpersonal contexts. Overall, the study emphasizes literature’s potential to illuminate the deep psychological consequences of bullying and to promote empathy toward individuals suffering from emotional wounds.